A pixelated approach to galaxy catalogue incompleteness: improving the dark siren measurement of the Hubble constant. Issue 1 (11th February 2022) - Gray, R; Messenger, C; Veitch, J
ABSTRACT: The use of gravitational wave standard sirens for cosmological analyses is becoming well known, with particular interest in measuring the Hubble constant, H 0, and in shedding light on the current tension between early- and late-time measurements. The current tension is over 4σ and standard sirens will be able to provide a completely independent measurement. Dark sirens (binary black hole or neutron star mergers with no electromagnetic counterparts) can be informative if the missing redshift information is provided through the use of galaxy catalogues to identify potential host galaxies of the merger. However, galaxy catalogue incompleteness affects this analysis, and accurate modelling of it is essential for obtaining an unbiased measurement of H 0 . Previously most methods have assumed uniform completeness within the sky area of a gravitational wave event. This paper presents an updated methodology in which the completeness of the galaxy catalogue is estimated in a directionally dependent matter, by pixelating the sky and computing the completeness of the galaxy catalogue along each line of sight. The H 0 inference for a single event is carried out on a pixel-by-pixel basis, and the pixels are combined for the final result. A reanalysis of the events in the first gravitational wave transient catalogue leads to an improvement on the measured value of H 0 of approximately 5 per cent compared to the 68.3 per cent highest density interval of the equivalent LIGO and Virgo result, with H 0 = 68.8^+15.9_-7.8 km s −1 Mpc −1 .